Penerapan Metode PPDIOO dalam Pengembangan LAN dan WLAN - Solikin, Imam (Teknomatika, 2017)
SMK Miftahul Huda is one of Private Vocational High School in Kecamatan Lempuing, Kabupaten Ogan Komering Ilir, Sumatera Selatan. This school has a LAN and Wireless LAN facilities related to the learning process. In the use of the facility LAN and Wireless LAN, students and teachers sometimes got into trouble while using WLAN for internet and other learning processes that use Wireless LAN or Wireless LAN network Internet due to unfavorable. Wireless LAN for network coverage, does not get a fairly wide area connections only Area in the laboratory course. Hence the need for a solution to these problems by applying methods PPDIOO in the development of LAN and WLAN. With the application of the method PPDIOO in the development of LAN and WLAN in Miftahu Huda, generating beneficiaries and the use of Wireless LAN network with stable connection and the connection area is wider not only around the lab alone but to other areas such as in the teacher's room, a library and more.Keywords : PPDIOO Method, LAN, WLAN